Key Factors In The Home Environment Contributing To The Low Pass Rates Of Primary Students In Selected Schools In Marondera District: A Comprehensive Review Using A Decision-Oriented Model - Chrispen Chiome; Prisca Mtizwa (CV. RADJA PUBLIKA, 2025)
This article uses a decision-oriented model to provide a comprehensive review of the key factors in the home environment of learners contributing to the low pass rates of primary students in selected schools in the Marondera District. The home environment plays a significant role in shaping a child's academic achievement, and various factors contribute to this influence. This review examines the relationship between home environment and academic performance, highlighting the key factors that impact learners' success. The study’s design was embedded mixed-methods research design. The sample comprised of two hundred and sixteen respondents and participants who were randomly and purposively selected. The study’s data collection and generation instruments were the questionnaire, document analysis, interview and observation. Qualitative data was analysed using the traditional thematic content analysis and quantitative data wase analysed using statistical methods. The key findings include parenting styles, education of parents, financial position of parents, resources for education in the home, attitudes of parents towards schooling, socio-economic context environment and parents’ conflict. The research concluded that there were serious impediments in the home environment that has affected learners. The study recommends multifaceted approach that also upgrades the school environment as a way of improving the pass rate of the children in this study. The study also recommends a vast supply of safety nets and equitable distribution thereof. As well as encouraging parents to create a home that is conducive for their children’s access to quality education.